(3GdeLdS GdOSJhQj hOhQg aj GdQbGHI Ydi GdGfJNGHGJ GdQFGSjI hGdJTQjYjI hYedjGJ GdGSJaJGA (B:s (3OQGSI ebGQfI (B: (3GdLRGFQ fehPLG (B: (3GdeLdS GdOSJhQj GdLRGFQj (B: (3bGVj GdGfJNGHGJ GdhWfjI (B/s - (3YHGS, HdZhds ((3GdbGgQI ;s (3GdchjJ ;s (3GdLRGFQ (B:s (3OGQ GdcJGH GdMOjK ddWHY hGdfTQ hGdJhRjY,s, 2015)
(3gPG GdcJGH jJfGhd ehVhY GdeLdS GdOSJhQj hOhQg aj GdQbGHI Ydi GdGfJNGHGJ GdQFGSjI hGdJTQjYjI hYedjGJ GdGSJaJGA(B-(3OQGSI ebGQfI hgPG jJVef (B: (3GdaUd GdChd (B: (3GdCSGS GdJGQjNj hGdbGfhfj ddQbGHI Ydi GdGfJNGHGJ, GdaUd GdKGfj (B: (3QbGHI GdeLdS GdOSJhQj Ydi YedjI GdGbJQGY, GdaUd GdKGdK (B: (3aUd GdeLdS GdOSJhQj aj GdWYhf hGdGMJLJLGJ(B.s
(3HHdjhLQGajI (B: (3UaMI (B397-435.s
Keywords: (3GdLRGFQ(B.s -- (3GdeLdS GdOSJhQjs; (3GdGSJaJGAs -- (3GdLRGFQs; (3GdQbGHI GdbVGFjIs -- (3GdLRGFQs; (3eQGbHI GdGfJNGHGJs -- (3bhGfjf hJTQjYGJs -- (3GdLRGFQs